2016
DOI: 10.2174/1385272820666160216225330
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Applications of POMs and Their Hybrids in Catalysis

Abstract: Polyoxometalates (POMs) and their hybrid systems are green and efficient catalysts which have found a wide range of application, due to their outstanding properties such as high thermal stability, Redox potential, strong Bronsted acidity, non-corrosive nature and sensitivity to electricity and light. They are able to catalyze various organic reactions as well as being involved in photocatalytic processes. In this review, we try to highlight the recent advances (2009)(2010)(2011)(2012)(2013)(2014)(2015) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 0 publications
1
62
0
Order By: Relevance
“…We recently published a review article regarding Pd(0) nanoparticles in which we disclosed the utility of mesoporous silica for the encapsulation of Pd nanoparticles. 13 In attempt to expand the concept of encapsulated catalysts 9,11,90,91 and in continuation of our recent review article on encapsulated catalysts, 13 herein we consider mesoporous silica materials from a new point of view and cover the recent advances (2014)(2015)(2016)(2017) in utility of the functionalized SBA mesoporous silica for embedding various catalytic species or second functionality for developing novel hybrid catalysts. Noteworthy, we make effort to highlight the advantageous of these state of the art catalysts.…”
Section: -86mentioning
confidence: 99%
“…We recently published a review article regarding Pd(0) nanoparticles in which we disclosed the utility of mesoporous silica for the encapsulation of Pd nanoparticles. 13 In attempt to expand the concept of encapsulated catalysts 9,11,90,91 and in continuation of our recent review article on encapsulated catalysts, 13 herein we consider mesoporous silica materials from a new point of view and cover the recent advances (2014)(2015)(2016)(2017) in utility of the functionalized SBA mesoporous silica for embedding various catalytic species or second functionality for developing novel hybrid catalysts. Noteworthy, we make effort to highlight the advantageous of these state of the art catalysts.…”
Section: -86mentioning
confidence: 99%
“…In the course of our research on heterogeneous catalysis, recently we reported the utility of CDNS and natural clays for immobilizing catalytic active species . In this line, it was found that the hybridization of inorganic supports with CDNS can lead to an improvement of the catalytic performance of the resulting catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant advances in this research field, development of a novel efficient, non‐toxic heterogeneous catalyst which could promote these reactions under green condition is still remained a hot topic. In continuation of our research on the design and preparation of heterogeneous catalysts and development of environmentally benign procedures for the synthesis of chemicals, recently, we focused on the utility of magnetic hollow spheres for developing hybrid magnetically separable heterogeneous catalysts . In this line, we developed efficient catalysts by decorating magnetic hollow spheres with organic functionalities such as dopamine and cyclodextrin and doping silver nanoparticles .…”
Section: Introductionmentioning
confidence: 99%